Prediction of perinatal outcome in high-risk pregnancy by Doppler ultrasound: a prospective cohort study - Karena, Zalak V.; Mehta, Aditya D.; Vaghela, Hetvee M.; Shah, Harsh R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Doppler study of uterine and fetal vessels assesses the feto-maternal circulation. An abnormal Doppler study is a sign of placental dysfunction and fetal damage. This study aims to study the relationship of Doppler velocimetry of the uterine artery, umbilical artery, and middle cerebral artery to perinatal outcomes in normal and high-risk pregnancies. Methods: A prospective cohort study was conducted in a tertiary health care center. A total of 150 patients aged 18–35 years with the gestational age of 28 to 40 weeks in 2 cohorts, 75 in high risk and 75 in the non-high-risk cohort were included. Pregnant women with gestational hypertension, intrauterine growth restriction, preeclampsia, preeclampsia plus IUGR were included in high-risk cohort. Doppler study was carried out, data was collected, and was analyzed. Results: Doppler parameters and their association with perinatal outcome were measured. The sensitivity of umbilical artery index (79.4%) was found to be highly predictive of poor neonatal outcomes compared to middle cerebral artery Doppler (58.8%) and cerebroplacental ratio (41.2%) parameters. A high positive predictive value for unfavourable perinatal outcomes with an accuracy of 93% using umbilical artery indices, 95% using MCA Doppler, and 93% CPR was found in the study. Specificity of umbilical artery Doppler was 87.5%, MCA Doppler was 93.75% and CPR was 93.75%. Conclusions: When incorporated into evaluating high-risk pregnancies complicated by pregnancy-induced hypertension, preeclampsia, and IUGR in the third trimester, screening the fetuses for well-being with Doppler helps in timely intervention and improves the perinatal outcome.